2018
DOI: 10.1088/1751-8121/aae9fc
|View full text |Cite
|
Sign up to set email alerts
|

Full-parameter discrete Painlevé systems from non-translational Cremona isometries

Abstract: Since the classification of discrete Painlevé equations in terms of rational surfaces, there has been much interest in the range of integrable equations arising from each of the 22 surface types in Sakai's list. For all but the most degenerate type in the list, the surfaces come in families which admit affine Weyl groups of symmetries. Translation elements of this symmetry group define discrete Painlevé equations with the same number of parameters as their family of surfaces. While non-translation elements of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
3
3
0
Order By: Relevance
“…In particular, it was found that in this embedding the element φ which give rise to W(A 1 × A 3 ) (1) type Painlevé equation is not a translation in W(D (1) 5 ), whereas the element φ 2 is translational. Similar examples have been found in different contexts in the integrable system literature [9][10][11][12]. A common feature of these examples is that the element φ which gives rise to a discrete Painlevé equation is not translational, whereas some powers of φ is.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In particular, it was found that in this embedding the element φ which give rise to W(A 1 × A 3 ) (1) type Painlevé equation is not a translation in W(D (1) 5 ), whereas the element φ 2 is translational. Similar examples have been found in different contexts in the integrable system literature [9][10][11][12]. A common feature of these examples is that the element φ which gives rise to a discrete Painlevé equation is not translational, whereas some powers of φ is.…”
Section: Introductionsupporting
confidence: 71%
“…Quasi-translations arise under different guises in a variety of contexts in the theory of discrete integrable equations. For example, in 'symmetrisation' procedures of asymmetric discrete Painlevé equations known as projective reductions [11,12]; from reductions of partial difference equations [9]; or as elements that give rise to discrete equations which govern evolutions of Schramm's circle patterns [10]. Normalizer theory of Coxeter groups are extremely rich, not only it explains 'elements of quasi-translational' nature found in the study of Painlevé equations, it is also constructive.…”
Section: Discussionmentioning
confidence: 99%
“…, whereas the element φ 2 is translational. Similar examples have been found in different contexts in the integrable system literature [6,15,1,5]. A common feature of these examples is that the element φ which gives rise to a discrete Painlevé equation is not translational, whereas some powers of φ is.…”
Section: Introductionsupporting
confidence: 70%
“…Quasi-translations arise under different guises in a variety of contexts in the theory of discrete integrable equations. For example, in "symmetrisation" procedures of asymmetric discrete Painlevé equations known as projective reductions [6,15]; from reductions of partial difference equations [1]; or as elements that give rise to discrete equations which govern evolutions of Schramm's circle patterns [5], these we plan to discuss in subsequent publications.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we show that these discrete systems admit symmetries that do not appear explicitly in Sakai's classification. Such two-dimensional discrete integrable systems have been found in different contexts [1,6,7,24,29,44,46]. In [42], it was found that these symmetries arise as normalizers of certain parabolic subgroups of Sakai's Weyl groups using the normalizer theory of of Coxeter groups [5,21].…”
mentioning
confidence: 99%